A case of intramandibular neurofibroma resembling a radicular cyst in a neurofibromatosis type 1 patient. (May 2021) - Kunisada, Yuki; Yoshioka, Norie; Ibaragi, Soichiro; Okui, Tatsuo; Nagatsuka, Hitoshi; Sasaki, Akira
Highlights: Neurofibromatosis is a disease that causes various abnormalities such as neurofibroma, mainly in the skin and nerves. The common sites of occurrence in the oral cavity are the palate, gingiva, etc., occurrence in the mandible is rare. The patient had already been prenatally diagnosed with neurofibromatosis type 1. The lesion was clinically diagnosed with a radicular cyst, but histopathological diagnosis showed a neurofibroma. Tumor extirpation was performed under general anesthesia. Abstract: Introduction: Neurofibromatosis is a disease that causes various abnormalities such as neurofibroma, mainly in the skin and nerves. The common sites in the oral cavity are the palate, gingiva, tongue, buccal mucosa, and lips but, occurrence in the mandible is rare. Presentation of case: A 26-year-old woman was referred to our clinic because of percussion pain. Radiographic findings showed a radiolucent area. The patient was clinically diagnosed with a radicular cyst by a previous doctor. Multiple café-au-lait spots were found disseminated on her body, and she had already been prenatally diagnosed with neurofibromatosis type 1 (NF1). We performed a biopsy and suggested a neurofibroma. Tumor extirpation was performed under general anesthesia. The histopathological diagnosis showed a neurofibroma. Clinical discussion and conclusion: NF1 is a systemic nevus that causes abnormalities in melanocytes and Schwann cells, and various lesions appear, but intramandibular lesions are extremely rare. Diagnosis of NF1 and radicular cysts in the mandible is difficult due to their image resemblance. However, it should be kept in mind if the underlying disease is NF1. In our case, it was easy to detach and may have originated from small peripheral nerve endings in the mandible.